Design of Microsleep Alerting System of Pilot to Reduce Air Accidents - M.S. Prabhu (International Journal of Engineering and Management Research, 2021)
The pilot’s micro sleep often caused by fatigue and/or drowsiness receives increasing attention for the last few years, especially after it became evident that pilot’s micro sleep also one of the major factor causing serious aircraft accidents. The system comprises EOG, EEG and IR module. EEG measures the electrical activity of the brain called brain wave pattern through intrusive electrodes. EOG tapes the electrical potential of eyeball movements and the IR module senses the eye blink frequency. Then all these signals are applied to a robust signal processing unit and microcontroller. When an indicating feature corresponds to the micro sleep events are detected, the warning system is activated. This envisioned micro sleep alerting system would continuously monitor the alertness of the pilot and provides immediate warning signal, when micro sleep detected with high certainty.